Development of Pop-up Book Learning Media to Improve Student Language Skills - Nadia Bismi Hafifah; Wisman Hadi; Mara Untung Ritonga (Randwick International of Education and Linguistics Science Journal, 2023)
Learning media has a big impact on the success of the teaching and learning process. This study aims to develop innovative and interactive pop-up book learning media, as well as knowing the practicality of the learning media of energy changes in energy. This study uses the Research and Development (R&D) approach using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The sample of this study was all students of Class III SD Negeri 169 Purba Julu, Kec Puncak Sorik Merapi with research instruments in the form of validation sheets of material, language, and design experts. The results showed that the pop-up book learning media developed energy changes had met the validators' criteria based on validator assessment with material validity value of 4.6 with a very feasible category, for the value of language validity of 4.7 with a very feasible category, and for values Design validity of 4.6 with a very decent category. Pop-up Book Learning Media Changes developed have met practicality criteria through: a) Teacher response questionnaire results to interactive teaching materials show practical values of 4.6 with a very practical category; b) The results of student response questionnaires to interactive teaching materials show a practical value of 4 with a very practical category.